Development of Learning Videos on Petroleum Materials Using Dora Toon Web Apps for Class XI High School Students - Rahmadhani*, Isnaini; Fikroh, Retno Aliyatul (Jurnal IPA & Pembelajaran IPA, 2024)
Many students have difficulty understanding chemistry concepts due to limited learning resources such as textbooks and traditional lectures. This research proposes making videos using Dora Toon, an audiovisual web platform specifically for petroleum materials. This project aims to assess video quality through evaluation by research subjects (material experts, media, chemistry educators, and 10 class XI high school students). With a research and development approach, the model used is 4D (define, design, development, disseminate) with a focus on the disseminate stage. The definition stage includes analysis of the front-end, students, concepts, tasks, and learning objectives. The design stages include selecting media format, collecting references, creating initial designs, and making instruments. The development stage includes video production, validation tests on research subjects. Sampling used purposive sampling technique, data collection used a validation questionnaire, and analyzed descriptively in percentages. At the disseminate stage, the product can be distributed to the wider community. However, this stage was not carried out due to time constraints. This results in HD resolution that is easy to use. It produces HD (1280x720p) resolution MP4 videos that are easy to use and contain petroleum ingredients. The evaluation results were very positive. The material expert gave a score of 95% (very good), the media expert gave a score of 95% (very good), the chemistry teacher gave a score of 86.06% (very good), and the students answered positively 100%. These findings indicate that animated videos can be an alternative learning tool for teaching petroleum chemistry in the classroom